Student Assignment, BioInformatics Final Project - Kramer, Paige; Treml, Jack (Midwestern Journal of Undergraduate Sciences, 2022)
This final project assignment can be used to implement the accompanying walkthrough in bioinformatics (or other applicable) classes.